Effect of Arabica Coffee Supplementation in a Skim Milk–Egg Yolk Extender on Plasma Membrane Integrity, Motility, Viability, and Abnormality of Boer Goat Spermatozoa - Khoiru Indana; Ni'mal Rabbana; Anhar Faisal Fanani; Dinar Anindyasari; Kirana Dara Dinanti Adiputra; Dede Aprylasari (Journal of Agriprecision & Social Impact, 2026)
This study evaluated the effect of Arabica coffee extract supplementation in a skim milk–egg yolk extender on sperm motility, viability, abnormality, and plasma membrane integrity in Boer goat semen. Semen was collected once weekly using an artificial vagina. A randomized block design with five treatments and four replicates was used: skim milk–egg yolk extender without coffee extract (P0) and extender supplemented with 0.2 (P1), 0.4 (P2), 0.6 (P3), or 0.8 mL (P4) of Arabica coffee extract. Semen was evaluated macroscopically for pH, volume, color, odor, and consistency and microscopically for motility, viability, abnormality, and plasma membrane integrity. Data were analyzed by analysis of variance using SPSS, followed by Duncan’s multiple range test. Fresh semen had a mean pH of 6.45 ± 0.55 and a volume of 1.175 ± 0.204 mL; it was yellowish white, had a characteristic odor, and exhibited a thick consistency. Arabica coffee extract supplementation significantly affected all microscopic parameters (p < 0.001). The 0.6 mL treatment (P3) produced the highest motility (74.50 ± 5.26%), viability (87.25 ± 6.34%), and plasma membrane integrity (90.00 ± 3.46%) and the lowest abnormality (17.00 ± 8.28%). These findings indicate that supplementation with 0.6 mL of Arabica coffee extract may improve the quality of Boer goat semen extended with skim milk–egg yolk.